You may solve your system using elimination.
Subtracting the second equation from the first yields:
6x + 5y - (-5x + 5y) = 61 - (-5)
Opening the brackets yields:
6x + 5y + 5x - 5y = 61 + 5
Removing opposite terms yields:
11x = 66
Dividing both sides by 11 yields:
x = 6
Plug 6 in the first equation:
6*6 + 5y = 61
Subtracting 36 both sides yields:
5y = 61 - 36 => 5y = 25 => y = 5
The solution to the given system is the ordered pair (6;5).
we can solve this by other method that is substituion method , it will be easy too and also it will require very few step to get the values of x and y. online college
This is not too hard you have to just find the values of x and y.substract the second equation from the first one then you got the value of x and just put it in any equation for y.used equipment